Cultura local e o processo de ensino e aprendizagem no campo da oralidade: uma perspectiva do professor e do aluno - COSTA, Rosângela Rodrigues da (2024)
This study proposes to theme the local culture and the process of teaching and learning in the field of orality from the perspective of a teacher and student. The aim of the research is to discuss the importance of knowledge of the local culture and its influence on school students' knowledge and how teachers use this knowledge to advance the learning process aiming orality through field research, analyzed the use of these methodological resources for professionals Sao Tome School. To the study development was performed the literature review to describe the theories that addressed the agrarian question and the rural environment, the teacher educational training partner amid changes especially the rural community center Camurituba so having an understanding of the pathways that lead to this type of education quality. On field research conducted in school São Tomé, a questionnaire was given to two teachers and two students and their answers brought relevant placements about the complexity of teaching academic content without loss of their familiar knowledge, because these communities to their cultural influence is very strong with children becoming a challenge to teachers. These questionings that formed the basis for the present work.